Teste de deterioração controlada em sementes de amendoim - Silveira, César Martoreli da [UNESP] (2006)
This research was carried out at the Seed Analysis Laboratory of the Crop Science Department, UNESP State University, Campus of Jaboticabal, São Paulo State, Brazil. The objective of this research was to evaluate the controlled deterioration in peanut seeds cv. IAC-886 (Runner). Were used five peanut seed lots got from the COPLANA cooperative, Jaboticabal County, São Paulo State. The seed quality was evaluated by the sand and paper germination test, first germination count, speed of emergence index, dry matter weight, accelerated aging, electrical conductivity, field seedling emergence, in comparison with controlled deterioration test. Was used for the germination and vigor test a complete randomized design with 08 replications. For the controlled deterioration test was used a factorial arrangement of treatments (5x2x3) consisting of 5 seed lots, 2 temperatures (40 and 450C) and 3 seed moisture contents (15, 20 e 25%) and a period of 48 hours in water bath with 05 replications. For the mean comparison was used the Tukey test at 5% probability. Was also made a correlation coefficient (r) between the germination and vigor tests. According to the obtained results was observed that the controlled deterioration test was very drastic for the seed germination and permitted to differentiate the vigor between seed lots. The combination 400C and seed moisture content of 20% was the best one to distinguish the difference of vigor between seed lots and didn't cause a deleterious effect on the seed germination, moreover were observed significative correlations with field seedling emergence test. The temperature of 450C and seed moisture content of 20 and 25% caused a drastic drop down in the seed germination.